The Integrating Food Pedagogy and Project-Based Learning to Promote Healthy Eating in Early Childhood: A Systematic Literature Review - Waliatun isnaini; Zakirman; Erie Siti Syarah; Siti Aisyah; Noviana Mustapa; Catherine Lie (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
Food insecurity remains a critical issue affecting early childhood health. Early food knowledge significantly shapes children’s dietary behaviors, underscoring the need for effective pedagogical integration within early education settings. This study aims to systematically examine the integration of food pedagogy and Project-Based Learning (PjBL) and to analyze its impact on children’s health knowledge and healthy food choices. This systematic literature review followed PRISMA guidelines. Peer-reviewed empirical studies published between 2014 and 2024 were retrieved from the Scopus database using predefined inclusion and exclusion criteria. Articles focusing on early childhood populations, food or nutrition education, and project-based or experiential learning approaches were selected. Data were extracted and synthesized thematically to identify instructional patterns and reported outcomes. The findings indicate that integrating food pedagogy within PjBL enhances nutritional knowledge, fosters positive attitudes toward healthy foods, and supports informed dietary decision-making. Evidence consistently shows that experiential and collaborative projects contribute to sustainable healthy eating behaviors in early childhood. Overall, food pedagogy implemented through project-based learning represents a promising approach to strengthening early preventive efforts against food insecurity.